An iterative method for the solution of inverse shaping problems under creep conditions - Bormotin, K.S. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2013)
Inverse shaping problems are formulated in the form of quasistatic deformation of bodies. An iterative method for the solution of inverse shaping problems under creep is proposed in the case of structural elements design. The proposed method is implemented as a software package of engineering analysis.